Proteomics in viral disease - Gangadharan, B (2006)
The separation, identification, and characterisation of the proteins present in a tissue or biological sample is called ‘proteomics’. This technique can be used for example to identify biomarkers and investigate signalling pathways. Increasingly, proteomics is being applied to the analysis of virus related samples; here two such examples are described. Presently there is no reliable non-invasive way of assessing liver fibrosis. Here a novel 2D-PAGE based proteomics study was used to identify potential fibrosis biomarkers. Serum from patients with varying degrees of hepatic scarring induced by infection with the hepatitis C virus (HCV) was analysed. Several proteins associated with liver scarring and/or viral infection were identified. The most prominent changes were observed when comparing serum samples from cirrhotic patients with healthy controls: Expression of inter-α-trypsin inhibitor heavy chain H4 fragments, α1 antichymotrypsin, apolipoprotein L1 (Apo L1), prealbumin and albumin was decreased in cirrhotic serum, whereas CD5 antigen like protein (CD5L) and β2 glycoprotein I (β2GPI) increased. In general, α2 macroglobulin (a2M) and immunoglobulin components increased with hepatic fibrosis whereas haptoglobin and complement components (C3, C4 and factor H-related protein 1) decreased. Novel proteins associated with HCV-induced fibrosis include the inter-alpha-trypsin inhibitor heavy chain H4 fragments, complement factor H-related protein 1, CD5L, Apo L1, β2GPI and the increase in thiolester cleaved products of a2M. The relationship between these changes is discussed. One of the accessory genes of the HIV viral genome encodes for the Nef protein. Nef is present in lipid rafts and increases viral replication within infected host cells by binding to a guanine nucleotide exchange factor, Vav. This leads to activation of a GTPase, Cdc42, however, the signalling pathway is poorly understood. 2D-PAGE based proteomics was used to identify differentially expressed raft-associated proteins by comparing T cells in the presence and absence of Nef. A ubiquitin conjugating enzyme UbcH7, which acts in conjugation with c-Cbl, was absent from the rafts of Nef-transfected cells. Vav ubiquitination was also absent from these rafts. In collaboration with Dr. Alison Simmons and Prof. Andrew McMichael the absence of UbcH7 in rafts was found to be caused by β-Pix forming a ternary complex with c-Cbl and activated Cdc42. Vav ubiquitination was restored and viral replication was diminished when β-Pix was knocked down providing a new candidate target for inhibiting HIV replication. This thesis demonstrates the use of proteomics in providing novel information for virus related samples. This influential technology benefits in both biomarker discovery to aid clinicians with early diagnosis of diseased individuals and in the elucidation of novel signalling pathways in infected cells to provide new candidate targets.